2017
DOI: 10.18203/2320-1770.ijrcog20170377
|View full text |Cite
|
Sign up to set email alerts
|

Trend of HIV seroprevalence among antenatal women at tertiary care hospital in North India, eleven years retrospective study

Abstract: Background: Human Immunodeficiency virus (HIV)/Acquired immunodeficiency syndrome (AIDS) is spreading worldwide at an alarming rate and India has third largest number of estimated people living with HIV/AIDS in the world. Estimating the HIV seroprevalence in a low risk population such as pregnant women provide essential information for monitoring trend of HIV in general population and assist in prevention from mother to child transmission (PMTCT) of HIV infection. Only few studies are available from this part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A comparable rate of 4.1% had been reported in Yenagoa [10], 3.0% in Port Harcourt [11] and 5.6% in Tanzania [12]. In contrast, several other studies have reported lower rates, 0.8% [13], 2.4% [14] and 0.3% [15]. These lower rates may suggest a steady decline in HIV-1 infection among pregnant women in general.…”
Section: Resultsmentioning
confidence: 51%
“…A comparable rate of 4.1% had been reported in Yenagoa [10], 3.0% in Port Harcourt [11] and 5.6% in Tanzania [12]. In contrast, several other studies have reported lower rates, 0.8% [13], 2.4% [14] and 0.3% [15]. These lower rates may suggest a steady decline in HIV-1 infection among pregnant women in general.…”
Section: Resultsmentioning
confidence: 51%